Giorgione’s Homage to the Eucharist - Schier, Rudolf (2025)
In the context of the Italian reformation movements in the fifteenth and sixteenth centuries, this paper examines the influence of the Transubstantiation and Real Presence controversies on Giorgione’s painting known as the Homage to a Poet. The picture is seen as a development of the treatment of this subject in Raphael’s frescos La Disputa and Mass at Bolsano and in the illustrations of the statute books of the Venetian Confraternities of the Most Holy Sacrament. Several analogies to the Allendale Nativity are noted. The main figure in Giorgione’s picture is identified as a fusion of the Man of Sorrows and Ecce Homo images, representing the Eucharist on the altar. The other figures are interpreted to be Aeneas, Tabitha, and Cornelius (Acts 10:34–43). The conversion of bread and wine into the body and blood of Christ is exemplified in the painting by the conversion narrative uniting these three secondary figures.
Keywords: Ecce Homo; man of sorrows; Transubstantiation; Acts of the Apostles; Schools of the Most Holy Sacrament; Raphael’s frescos; Homage to a Poet; Giorgione